The Effectiveness of Deep Learning Approaches in Improving Literacy and Numeracy in Geography Learning - Pradika Adi Wijayanto; Juhadi Juhadi; Apik Budi Santoso; Muhammad Guruh Bintang Wicaksana; Shinta Kusumaningjati; Fajar Wahyushi Fuedsi (Jurnal Pemberdayaan Masyarakat, 2026)
This study aims to implement and test the effectiveness of a Deep Learning approach that integrates literacy and numeracy competencies into Geography learning. The study is motivated by the absence of a standardized and comprehensive Deep Learning teaching module format adaptable to various Geography topics at the secondary school level to strengthen students' literacy and numeracy skills. This research developed teaching modules, student worksheets, and an information technology–based learning media called "Geo Hepi" on climate and weather material at SMAN 12 Semarang. The research method used a pre-experimental design with a one-shot case study model and a quantitative approach. The research subjects were selected through purposive sampling, namely, class XE students. Data were collected using validation questionnaires, participatory observation sheets, and documentation, and analyzed descriptively using percentage techniques and interval criteria. The results showed that students' literacy and numeracy skills were in the good category, with literacy at 89% and numeracy at 87% in the first meeting, and 88% and 83% in the second meeting. These findings indicate that the Deep Learning approach is effective in improving students' literacy and numeracy competencies in Geography learning.